(untitled) (Research, Society and Development, 2021)
The research records of the last decade bring a systemic look, which involves historicity and triggers strategies with perspectives to solve problems and dilemmas that involve the educational context. The article addresses the difficulties that teachers have in integrating ICT as a motivating tool for the problem of the lack of interest of students in chemistry classes. The observation was made with chemistry teachers from thirteen public schools in the city of Manaus in the Midwest Zone, the State Department of Education of Amazonas - SEDUC. The results obtained through the questionnaires applied were tabulated and analyzed using the Likert scale, demonstrating how insufficient this integration is. The implications of this research address the difficulties that need to be overcome in relation to the computational thinking of chemistry teachers, bringing perspectives on the need for continuing education courses for professionals involved with this science.